Content Validity and Inter-Rater Reliability in Developing Minimum Competency Assessment Test Instruments (AKM) - Umami, Zalika; Suharini, Erni; Sholeh, Muh. (Journal of Research and Educational Research Evaluation, 2023)
This research aims to describe the results of validation by experts regarding the development of AKM test instruments in class XI geography subjects. This research is development research (R&D) with the research model used, namely the 4-D model (design, define, develop, disseminate). The product in this research is the AKM test instrument in class XI Geography. This expert validation involved 4 validators including 1 evaluation expert lecturer, 1 geography education expert lecturer, and 2 geography subject expert teachers. The tests carried out by experts are the AKM test instrument assessment test and the validity and reliability test results of the AKM test instrument. The results of this research are the AKM test instrument with expert assessment results based on language of 87% which is in the very good category, 87% of the construction aspect is in the very good category and 89% of the material aspect is in the very good category. Furthermore, the validity assessment by experts related to the development of the AKM test instrument obtained a v'Aikens index test result of 0.8125 which was included in the very valid criteria. The results of the reliability test showed that Avage Measures was 0.686, which is included in the ICC criteria for good reliability. In this way, the overall development of the AKM test instrument is valid and can also be used by educators as a reference in developing the AKM test instrument to support students' abilities.